2021
DOI: 10.3390/ani11123508
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Genotype and Age on Energy and Protein Utilization in Individually Housed Brown Laying Hens

Abstract: Responses to dietary energy and protein levels were compared between two egg-laying genotypes. Individually housed hens of a historic strain (HS) and a modern strain (MS) were compared. In Experiment 1 (Exp.1), four levels of true metabolizable energy, corrected for zero nitrogen retention (TMEn) and four levels of total lysine, were offered from 30 to 40 weeks of age. In Experiment 2 (Exp.2), three levels of apparent metabolizable energy, corrected for zero nitrogen retention (AMEn) and four levels of standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The results indicated that the Sapu-sapu fish is rich in minerals observed from the Sapu-sapu fish body, which has a hard layer of skin and a large head with hard bones. The mineral content found in this fish, especially Ca and P, is excellent to be used as a source of minerals to form egg shells and bones (Lukic et al 2009;Eleroğlu et al 2017;Kleyn et al 2021). The Ca and P mineral content in Sapusapu fish is relatively high at 4.26±0.0001% and 0.99±0.004%.…”
Section: Mineral Content Of Sapu-sapu Fishmentioning
confidence: 90%
“…The results indicated that the Sapu-sapu fish is rich in minerals observed from the Sapu-sapu fish body, which has a hard layer of skin and a large head with hard bones. The mineral content found in this fish, especially Ca and P, is excellent to be used as a source of minerals to form egg shells and bones (Lukic et al 2009;Eleroğlu et al 2017;Kleyn et al 2021). The Ca and P mineral content in Sapusapu fish is relatively high at 4.26±0.0001% and 0.99±0.004%.…”
Section: Mineral Content Of Sapu-sapu Fishmentioning
confidence: 90%